Basic fibroblast growth factor-encapsulated PCL nano/microfibrous composite scaffolds for bone regeneration. (12th October 2015) - Park, Ko Eun; Kim, Beom Su; Kim, Min Hee; You, Hyung Keun; Lee, Jun; Park, Won Ho
Abstract: Basic fibroblast growth factor (bFGF)-encapsulated poly(ε-caprolactone) (PCL) nano/microfibrous scaffolds were fabricated to improve cell viability and tissue regeneration. bFGF-encapsulated PCL nanofibers and microfibers were fabricated by emulsion electrospinning and melt-electrospinning, respectively. Electrospinnability of emulsions was improved with the addition of Pluronic F-127 because emulsions containing Pluronic F-127 had a high affinity for both water and oil phases. The core–shell structure of protein-encapsulated nanofiber component was observed by a confocal laser scanning microscope (CLSM). From results of CLSM observation, it was found that the protein-loaded particle's size and their loading efficiency inside nanofibers were influenced by the addition of emulsifiers and the concentration thereof. Also, the 'Protein/SA' group contained a viscoelastic water phase with smaller particles in the core of nanofibers than the 'Protein only' group does. From protein release behavior, it was apparent that protein-encapsulated nanofibers prepared by emulsion electrospinning were stable in water environments and were only released in Na ion-containing medium such as bodily fluids. In vitro cell proliferation, the optical density of the 'Protein/SA' group with bFGF at 490 nm was slight higher than that of the 'None' and 'Protein only' group during the period of cell culture. In vivo bone regeneration, bFGF-encapsulated nano/microfibrous composite scaffold is the only group that new bone was formed to the center of the defect. Consequently, the potential use of bFGF-encapsulated nano/microfibrous composite scaffolds in bone regeneration fields was suggested. Graphical abstract: Highlights: bFGF-encapsulated PCL nanofibers and microfibers were fabricated by electrospinning. New bone was formed by bFGF-encapsulated nano/microfibrous composite scaffold. Nano/microfibrous composite scaffolds have a potential use in bone regeneration fields.